PREDIKTOR PERILAKU SEKS BEBAS REMAJA SMA - ., Widyoningsih; ., Sutarno (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Adolescence is defined as the transitional period from childhood to adulthood. The adolescent age limit according to the World Health Organization (WHO) is 12 to 24 years. The impact of teenage free association leads to social tuna activities in the community. Data from Cilacap District Health Office 2010 through Youth Reproduction Health program (KRR) found that there are 44 Unwanted Pregnancy (KTD) in the work area of ​​Puskesmas. in adolescents have a very serious impact for adolescents themselves, in the form of biological, psychological and social impacts. The purpose of this study was to determine predictors of pre-marital sex behavior in high school adolescents in Cilacap District. The research design is descriptive quantitative. The population in this study are high school adolescents and SMK SR. The sampling technique used in this research is cluster random sampling. The sample size is 30 people. The results showed that adolescent attitudes about free sex were mostly in the negative attitudes category of 30 people (100%) adolescent religiosity levels were mostly in the good category of 3 people (10%) and enough (90%). Behavior near 100% is risk. From this data it can be concluded that 100% of high school adolescents and SMK SR have predictors of free sex behavior. Keywords: Predictors, sex behavior, high school adolescents